71.7k views
3 votes
Help me with this pls like omg soooo stressful

Help me with this pls like omg soooo stressful-example-1
User Rodris
by
4.7k points

2 Answers

4 votes

Answer:

t = 1

Explanation:

start by distributing the 4 to whats in the parentheses.

4 (-3 - 3/4t)

-12 - 3t

*helpful tip: if you multiply a fraction by its denominator the product is equal to its numerator

now you have:

3t - 18 = -12 - 3t

add 18 to both sides

3t = 6 - 3t

add 3t to both sides

6t = 6

divide both sides by 6

t = 1

User IceCreamToucan
by
5.3k points
4 votes

Answer:

t =1

Explanation:

3t - 18 = 4(-3-3/4t)

Distribute

3t - 18 = -12 -3t

Add 3t to each side

3t -18+3t = -12 -3t+3t

6t -18 =-12

Add 18

6t -18+18 = -12+18

6t = 6

Divide by 6

6t/6 = 6/6

t =1

User FuryComputers
by
5.6k points